Kesiapan Regulasi Hukum Siber di Indonesia dalam Menghadapi Ancaman Global: Studi Banding dengan Uni Eropa dan Amerika Serikat - Muhammad Taufik Rusydi; Gesang Kristianto Nugrohotomo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
In the increasingly developing digital era, cyber law regulation has become a crucial element in maintaining security and order in cyberspace. Indonesia, as a country with rapid technological growth, faces major challenges in responding to global threats in the cyber sector. This study aims to analyze the readiness of cyber law regulation in Indonesia by comparing it to the regulations implemented in the European Union and the United States. A qualitative approach is used with descriptive and normative analysis methods to examine the applicable cyber law policies. The results of the study show that Indonesia still has many limitations in cyber law enforcement, especially in terms of data protection, cybercrime, and coordination mechanisms between related institutions. On the other hand, the European Union already has a comprehensive General Data Protection Regulation (GDPR), while the United States applies a sectoral approach with different regulations in each field. This study suggests the need for regulatory reform that is more adaptive and responsive to global threats, as well as increased international cooperation in cyber law enforcement. Thus, Indonesia can be better prepared to face increasingly complex cyber challenges.